The cost of fair pay: How child care work wages affect formal child care hours, informal child care hours, and employment hours - Verena Löffler (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
The debate on the effects of child care policies on household and individual behavior is substantial but lacks a discussion of the unintended consequences of rising wages in the child care work sector. To address this gap in the debate, the relation between rising pay and formal child care hours, informal child care hours, and employment hours is analyzed empirically with a case study on child care in Germany between 2012 and 2019. Among other findings, the evidence demonstrates that the consumption of formal child care hours of middle- and high-income households in eastern Germany correlates negatively with child care work wages, indicating price elasticity.
Keywords: J13; J22; J38; 330; care work wage; early childhood education and care; informal child care; employment hours